Contextualized Supervisory Management and Principal Performance: A Comparative Analysis of Administrative Stabilization and Transformational Innovation - Rohmat Rohendi; Helmawati (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the supervisory management practices of school supervisors in Pagelaran and Sukanagara Districts, focusing on how contextual conditions shape supervisory approaches and outcomes. Using a qualitative comparative design, the research employed in-depth interviews, participant observations, document analysis, and member checking to ensure data validity. A total of 56 interviews, 32 observations, and 48 administrative documents were analyzed using thematic coding supported by NVivo 12. Findings reveal that both districts operate within identical structural mandates but demonstrate markedly different supervisory trajectories. In Pagelaran, supervision centers on administrative stabilization due to significant foundational gaps such as incomplete school planning documents and limited managerial capacity among principals. A directive, compliance-oriented model proved effective, resulting in a 57 percent increase in administrative adherence. In contrast, Sukanagara exhibits a more advanced supervisory ecosystem characterized by reflective coaching, collaborative problem-solving, design thinking sessions, and peer-based supervision. This developmental model stimulated substantial innovation, with schools producing an average of 2.3 new programs per semester and sustaining 78 percent of them. The study concludes that effective supervision must be adaptive, sequenced, and aligned with school readiness levels. Administrative reinforcement is essential in low-capacity contexts, while collaborative and transformative strategies thrive in schools with stronger cultural and organizational maturity. The research contributes to supervisory theory by highlighting the importance of contextual differentiation and ecosystemic perspectives in supervision, and it recommends policy reforms related to supervisory workload, digital systems, and differentiated competency development.